1981
DOI: 10.1152/ajpendo.1981.240.2.e88
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal canine starvation on fetal and neonatal liver metabolism

Abstract: Heptic glycolytic and gluconeogenic intermediates from fasted newborns of five control and five 3-day starved canine mothers (MCS) were studied at 0, 3, 6, 9, and 24 h of age. MCS did not affect fetal hepatic glycogen concentration; however, a significant increase in uridine diphosphate glucose (UDPG) (0.186 vs. 0.106 mumol/g), fructose 6-phosphate (0.084 vs. 0.034), pyruvate (0.321 vs. 0.126), and citrate (0.190 vs. 0.140) concentrations occurred. At 3 h, the intrahepatic glucose concentration among the MCS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 13 publications
4
18
0
Order By: Relevance
“…Thus, the conditions under which fetal hepatic redox state were determined were probably similar for all three groups. The fetal hepatic metabolite concentrations and energy and redox states in our study are similar to values reported by others for the fetal rat (5,11) and dog (19) in which the rapid killing technique was used. This method of fetal sampling is preferable to using anesthesia that can cause maternal hypoventilation (4) and result in artifactual changes in fetal redox and energy states (20).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the conditions under which fetal hepatic redox state were determined were probably similar for all three groups. The fetal hepatic metabolite concentrations and energy and redox states in our study are similar to values reported by others for the fetal rat (5,11) and dog (19) in which the rapid killing technique was used. This method of fetal sampling is preferable to using anesthesia that can cause maternal hypoventilation (4) and result in artifactual changes in fetal redox and energy states (20).…”
Section: Methodssupporting
confidence: 89%
“…Fetuses of maternal rats fasted for 96 h who have limited glucose provision but normal gaseous exchange have decreased hepatic ATP/ADP and adenylate charge ratios but normal redox states (5). However, fasting the pregnant dog significantly increases fetal lactate, AC, and BOHB concentrations and diminishes both fetal hepatic adenylate charge ratio and redox state (19,24). Fetal rats rendered hypoxic and hypercarbic have both diminished hepatic energy and redox states (20), whereas graded hypoxia in the 2-d-old rat pup decreases hepatic adenylate charge ratio and mitochondrial and cytoplasmic redox states (22).…”
Section: Methodsmentioning
confidence: 99%
“…F6P, fructose-6-phosphate G6P, glucose-6-phosphate MATERIALS AND METHODS P-creatine, phosphocreatine PEP, phosphoenolpyruvate Materials. Reagents and enzymes were analytical grade and Pyr, pyruvate purchased from commercial sources as reported in prior reports UDPG, uridinediphosphoglucose (26,29). Glucose (Mallinckrodt, St. Louis, MO) and galactose (Sigma, St. Louis, MO) were free of detectable contamination from galactose or glucose, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose concentrations may decline more rapidly a standard canine diet, and had their pups delivered at term by while alternate fuel provision may also be deficient as plasma free cesarean section as described previously. Pups were dried and kept fatty acid, glycerol or ketone body concentrations fail to rise warm in a heated, humidified incubator (26,29). Catheters were during neonatal fasting among mammals (9,12,13,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation